216k views
0 votes
40 Points? Solve & Explain

40 Points? Solve & Explain-example-1
User Pdxleif
by
5.7k points

2 Answers

5 votes

Answer:

(-1, 17)

Explanation:

User Jchavannes
by
5.1k points
3 votes

Answer:

(-1, 17)

Explanation:

The vertex form of a quadratic equation:


y=a(x-h)^2+k

(h, k) - vertex


y=x^2+2x+18


y=x^2+2(x)(1)+1^2-1^2+18 use (a + b)² = a² + 2ab + b² (*)


y=\underbrace{x^2+2(x)(1)+1^2}_((*))-1+18


y=(x+1)^2+17\\\\y=(x-(-1))^2+17

h = -1, k = 17

User Adu
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.